Evaluation of Novel Picolinamide Fungicides (QiI) for Controlling Cercospora beticola Sacc. in Sugar Beet - Akos F. Biró; Andy J. Leader; Andrea Hufnagl; Gábor Kukorelli; Zoltán Molnár (Horticulturae)
Studies were initiated to find new effective fungicides to use under field conditions to discover novel approaches for optimizing disease management in sugar beet crops. Cercospora leaf spot (CLS), a prevalent foliar disease in sugar beet crops worldwide, is caused by the fungal pathogen Cercospora beticola Sacc. This disease has become the most prevalent pathogen in sugar beet crops across nearly all European growing regions, including Hungary. The epidemic spread of this disease can cause up to 50% yield loss. The use of fungicides has been a cornerstone in managing CLS of sugar beet due to the limited efficacy of non-chemical alternatives. However, the emergence of fungicide-resistant strains of Cercospora beticola Sacc. in recent decades has compromised the effectiveness of certain fungicides, particularly those belonging to the QoI (FRAC Group 11) and DMI (FRAC Group 3) classes. Hungary is among the many countries where resistance to these fungicides has developed due to their frequent application. Picolinamides represent a novel class of fungal respiration inhibitors targeting Complex III within the Quinoine-Inside Inhibitor (QiI) group. Two innovative fungicides from this class, fenpicoxamid and florylpicoxamid (both classified under FRAC Group 21), were evaluated for their efficacy in managing CLS of sugar beet in Hungary during the 2020 and 2021 growing seasons. Both fungicides were applied as formulated products at various application rates and demonstrated superior efficacy in controlling CLS compared to untreated control plots and the reference fungicides difenoconazole and epoxiconazole. The results consistently demonstrated that all tested application rates of fenpicoxamid and florylpicoxamid effectively controlled CLS in sugar beet, exhibiting a clear dose–response relationship. Disease severity, as measured by the area under the disease progress curve (AUDPC), was significantly correlated with yield reduction but showed no significant association with root sugar content. Moreover, data from both study years indicated that picolinamide fungicides applied at a rate of 75 g ai/ha significantly outperformed difenoconazole (100 g ai/ha) in controlling the CLS of sugar beet. Additionally, higher application rates of picolinamides at 100–150 g ai/ha outperformed epoxiconazole at 125 g ai/ha in disease suppression. Fenpicoxamid is currently registered for use in cereals within Europe, and outside of Europe in Banana against Black Sigatoka (eff. Mycosphaerella fijiensis). Florylpicoxamid, while not yet registered in Europe, is undergoing approval processes in various countries worldwide for a range of crops and is continually being evaluated for potential market introduction. Additional details regarding the efficacy of florylpicoxamid against CLS in sugar beet were presented at ‘The 10th International Conference on Agricultural and Biological Sciences (ABS 2024, Győr-Hungary)’ in 2024.